Peer-to-Peer Support in Mathematics Education: Its Effectiveness for College Students in Mindanao State University-Sulu - Idris, Nasra (Journal of Interdisciplinary Perspectives, 2024)
This study assessed the extent of effectiveness of peer-to-peer support for college students in Mindanao State University-Sulu in the contest of study groups, peer review and mentoring. It employed descriptive-correlational research design with 100 student-respondents taken through simple random sampling method. Frequency distribution and percentage, mean and standard deviation, one-way analysis of variance (ANOVA) and Pearson product-moment correlation were the statistical methods used in the study. The following are findings of this study: Of the 100 student-respondents, majority are 20-21 years old, female, 2nd year level, and from the college of Arts and Sciences; The student-respondents agree on the extent of effectiveness of all three variables of peer-to-peer support for college students at Mindanao State University-Sulu; No significant difference in the extent of the effectiveness of peer-to-peer support for college students at Mindanao State University-Sulu when data are grouped according to their demographic profile in terms of age, gender, year level and course; And, generally, there is a significant positive correlation among the sub-categories subsumed under the extent of effectiveness of peer-to-peer support for college students in terms of study groups, peer review and mentoring. This study recommends the following: School heads should impose and support the implementation of peer-to-peer support programs in their institutions to improve the learning outcomes and academic performance of their students in mathematics; Mathematics Teachers should facilitate and implement the use of peer-to-peer support among their students to enhance their motivation and collaboration in learning mathematics; Mathematics teachers should practice their students on how to manage effective study groups, peer review, and peer mentoring sessions; Parents should support and encourage their children to participate in peer-to-peer support activities to help them develop their social skills; Students should actively engage in peer-to-peer support with their classmates to improve their understanding and confidence in learning mathematics; and Future researchers should conduct further studies on the effectiveness of peer-to-peer support for college students especially in different contexts and disciplines.